Fowl Immunoglobulins: Quantitation in Birds Genetically Resistant and Susceptible to Marek's Disease - Higgins, D. A. (1975)
The development of serum immunoglobulins was observed in chicks genetically resistant (N line) and susceptible (P line) to Marek's disease (MD), in conditions free from infection with MD. IgG was present at hatching at about 5.0 mg/ml and decreased to about 0.5 mg/ml by 12 to 15 days. Active production of IgG was apparent at about 20 days of age and reached levels of 2.0 to 3.0 mg/ml by 67 days. Low levels of IgM were present at hatching, and a gradual increase was seen to 1.0 to 2.0 mg/ml by 67 days. IgA was not detectable at hatching; it appeared in N-line birds at 5 days and in P-line birds at 13 days, and by 67 days was about 0.10 to 0.13 mg/ml. After 30 to 40 days, immunoglobulin levels were generally higher in N-line than in P-line birds. However, it was concluded that no primary immunoglobin deficiency existed sufficient to explain the susceptibility of the P-line birds to MD